2014
DOI: 10.1530/eje-14-0337
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insulin resistance and risk of diabetes mellitus in HIV-infected patients receiving current antiretroviral drugs

Abstract: Objective: HIV-infected patients had a higher prevalence of insulin resistance (IR) and risk of diabetes mellitus (DM) than that observed in healthy controls, but there are no data about the current prevalence considering the changes in HIV presentation and the use of newer antiretroviral drugs. Design: Longitudinal study which involved 265 HIV patients without DM, receiving first (nZ71) and advanced lines of antiretroviral therapy (nZ194). Methods: Prevalence of IR according to clinical and anthropometric var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 59 publications
8
45
3
Order By: Relevance
“…The prevalence of diabetes is higher in both pre-ART (13.2%) and ART (5.1%) cases, which is similar to a finding from Spain. 14 The prevalence of DM in the ART group is slightly lower than in a report from Jimma in the southwestern part of the country (8.5%), while the prevalence among pre-ART groups is higher than in the report from the southwest (0.9%). 5 The observed high prevalence of DM in the pre-ART group is confounded by a family history of DM; in this study, the number with a family history of DM in the pre-ART group was 13 (8.18%), while it was 11 (4.01%) in the ART group.…”
Section: Key Resultscontrasting
confidence: 57%
“…The prevalence of diabetes is higher in both pre-ART (13.2%) and ART (5.1%) cases, which is similar to a finding from Spain. 14 The prevalence of DM in the ART group is slightly lower than in a report from Jimma in the southwestern part of the country (8.5%), while the prevalence among pre-ART groups is higher than in the report from the southwest (0.9%). 5 The observed high prevalence of DM in the pre-ART group is confounded by a family history of DM; in this study, the number with a family history of DM in the pre-ART group was 13 (8.18%), while it was 11 (4.01%) in the ART group.…”
Section: Key Resultscontrasting
confidence: 57%
“…After a follow-up of 5.2 years, the DAD study revealed a crude incidence of new diabetes of 4.2 cases per 1000 person-years, which is similar to that described in the Swiss cohort (4.6 cases per 1000 person-years) [16,17]. In Spain, Araujo et al [18] reported that the rate of incident diabetes was 2.85 cases per 100 person-years in HIV-infected patients.…”
Section: Introductionsupporting
confidence: 60%
“…A longitudinal study of insulin resistance (IR) in PLWH on newer ART regimens identified IR in 21% of participants, which represents a significant decrease from estimates of 35–63% prevalence IR with older ART regimens. [57] However, the decrease in IR occurred alongside an increase in diabetes diagnoses and obesity prevalence. Diabetes prevalence estimates in PLWH range as high as 14%, but (1) vary significantly depending on the population studied, (2) often do not distinguish between type 1 and type 2 diabetes, and (3) do not include estimates of PLWH with undiagnosed diabetes.…”
Section: Metabolic Complications Are Increasing Among People Living Wmentioning
confidence: 99%